Population pharmacokinetics of ceftazidime in critically ill children: impact of cystic fibrosis. (26th May 2020) - Bui, S; Facchin, A; Ha, P; Bouchet, S; Leroux, S; Nacka, F; Fayon, M; Jacqz-Aigrain, E
Abstract: Background: Pharmacokinetics data on ceftazidime are sparse for the paediatric population, particularly for children with cystic fibrosis (CF) or severe infections. Objectives: To characterize the population pharmacokinetics of ceftazidime in critically ill children, identify covariates that affect drug disposition and evaluate the current dosing regimens. Methods: The study was registered with Clinicaltrials.gov (NCT01344512). Children receiving ceftazidime were selected in 13 French hospitals. Plasma concentrations were determined by UPLC-MS/MS. Population pharmacokinetic analyses were performed using NONMEN software. Results: One hundred and eight patients, aged 28 days to 12 years, with CF ( n  =   32), haematology and/or oncology disorders ( n  =   47) or severe infection ( n  =   29) were included. Ceftazidime was administered by continuous or intermittent infusions; 271 samples were available for analysis. A two-compartment model with first-order elimination and allometric scaling was developed and covariate analysis showed that ceftazidime pharmacokinetics were also significantly affected by CLCR and CF. Ceftazidime clearance was 82% higher in CF than in non-CF patients. Monte Carlo simulations showed that the percentage of target attainment (PTA) for the target of T >MIC   =   65% was (i) lower in CF than in non-CF children with intermittent infusions and (ii) higher with continuous than intermittent infusion in all children. Conclusions: The population pharmacokinetics model for ceftazidime in children was influenced by body weight, CLCR and CF. A higher PTA was obtained with continuous versus intermittent infusions. Further studies should explore the benefits of continuous versus intermittent infusion of ceftazidime, including current versus increased doses in CF children.